Upaya Peningkatan Pengetahuan Masyarakat dalam Budidaya Maggot BSF Sebagai Pengurai Limbah Organik - Putri Aurelia Shaquilla; Muhammad Luthfi Karuniaji; Sjarief Hidajat (CV. ALIM'SPUBLISHING, 2024)
This community service program aims to enhance the knowledge of the residents of Desa Bicak, Trowulan, Mojokerto, about Black Soldier Fly (BSF) maggot cultivation as a solution for organic waste management. The program involved 20 PKK members who were previously unfamiliar with maggots and their role in decomposing organic waste. The program was conducted in three stages: theoretical education, practical demonstration, and independent home implementation. The results showed an increase in participants' understanding of maggot cultivation techniques and the potential of maggots to reduce organic waste by up to 55%. In conclusion, the program successfully contributed to the promotion of SDGs No. 12 in Desa Bicak. It is hoped that this initiative will inspire positive changes in sustainable waste management within the community.